Aquatic Ecosystems: A Review on Prospecting of Anticancer Molecules from Fungi & Other Microbes - Mukesh Chander; Jasmeet Kaur (International Journal of Fungi, 2024)
Marine biota; namely, actinomycetes, bacteria, fungi, microalgae, green algae, oceanic weeds, mangroves, and other extremophiles constitute about 90% of the oceanic biomass. The organisms are taxonomically diverse, biologically productive/active, and biochemically unique. These unique biochemiques may act as a great source for the discovery of new bioactive molecules, including anticancer drugs. The marines produce medicinally potent biochemicals; namely, sulfated saccharides, polyphenols, and, sterols. Only a few of these alkaloids have been studied for their pharmacological properties; namely, antitumor, immunostimulatory, and antioxidative activities. The phytochemicals may probably interact with macrophages, initiating cell death and prevent mutational damage to DNA, reducing event of carcinogenesis. Peptides are bioactive products, which are inherent to many marine species. These marine peptides are of immense nutraceutical and medicinal importance as they have broad range of bioactivities, including microbicidal, antiviral, antimelanoma, antioxidative, cardioprotective, immunomodulatory, analgesic, anti-anxiety, anti-diabetic, appetite suppressing, and neuroprotective activities which have attracted the attention of the pharmaceutical industry, which attempts to modify them for treatment, cure, and prevention of various diseases. Some of these peptides and their derivatives are highly valuable commercially and developed as pharmaceutical and nutraceuticals commercially. The marine habitat, little explored, may act as a potential source of novel bioactive compounds acting as prospective and potent biopharmaceuticals. The biologically and the artificially synthesized/modified form of these chemicals may prove as novel therapeutic agents. The recent progress in technology and deep-sea exploration missions have made the drug discovery from oceanic sources a reality, resulting in screening, isolation, and modification of drugs capable of curing cancer, Parkinson’s, Alzheimer’s, and various other uncurable disorders and diseases. The available technology and use of modern gadgets have brought the depths of ocean within human approach and now marine resource like sponges, corals, etc., can be studied for their potential utilization in biopharmaceutical industry. In future, various types of bioactive compounds discovered for treating the diseases and these marine bioactive compounds are very beneficial and have no side effects.
Keywords: Bioactive Molecules; Microbes; antioxidant; antitumor; biopharmaceuticals